Obtenção e caracterização de hidrolisados enzimáticos de proteínas do farelo de soja - Miranda, Liceres Corrêa de (Universidade Federal de São Carlos, 2012)
Soy protein concentrate (SPC) is used as an ingredient for food and animal feed. It is obtained from defatted soybean meal by extracting sugars and other soluble compounds. The main consequence of the extraction process is removal or inactivation of most anti-nutritional factors of soybean, which makes this product can be used in place of animal proteins in special diets. This work aimed to study the process of protein hydrolysis as an alternative to increase the value of the SPC through the improvement of their nutritional value. Hydrolysis process has been done many years ago with the purpose of improving physico-chemical, organoleptic and nutritional value of food proteins. Enzymatic hydrolysis is the most appropriate when the objective is to improve the nutritional value, because the chemical methods cause many unwanted effects. We studied two commercial alkaline proteases, Alcalase® and Novo-ProD®. Novo-ProD® showed superior activity than Alcalase® in all pH conditions tested. The process conditions that maximized efficiency of the hydrolysis of SPC by Novo-ProD® were: 55°C, pH 9 and enzyme/substrate ratio of 0.5% (enzyme mass / protein mass). The maximum degree of hydrolysis obtained in three hours reaction under these conditions was approximately 15.2% in bench scale and 12.8% in pilot scale. Increasing solid concentration of the reaction medium from 10 to 30%, maximum degree of hydrolysis of 11.2% was obtained in the same conditions. Digestibility trial was conducted with SPC hydrolyzate with 3,3% against SPC unhydrolyzed in adult dogs and turkeys in the initial growth phase. In dogs, hydrolysis increased apparent digestibility of dry matter from 76.5 to 86.2%, crude protein from 83.9 to 90.6% and metabolizable energy increased by approximately 5%. In turkeys, the increase was from 54.6 to 62.9% for dry matter digestibility and 9% increase in metabolizable energy.
Keywords: Tecnologia de alimentos; Hidrólise de proteínas; Soja; Enzimas; Concentrado proteico de soja; Novo-Pro D®; Soy protein concentrate; Protein hydrolysis; Novo-ProD®; ENGENHARIAS::ENGENHARIA QUIMICA